2008
DOI: 10.1007/s00383-008-2117-9
|View full text |Cite
|
Sign up to set email alerts
|

A new technique for treatment of tracheal compression by the innominate artery: external reinforcement with autologous cartilage graft and muscle flap suspension

Abstract: We report a new technique for treatment of tracheomalacia or tracheal compression caused by the innominate artery, utilized in two patients with neuromuscular disorders. Both cases developed a chest deformity in the setting of severe scoliosis. Computed chest tomography and fiberoptic bronchoscopy showed that the cervical trachea was compressed between the innominate artery and the cervical spine in the setting of deformity of the thoracic cavity. Both patients required prolonged mechanical ventilation prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…2 Reimplantation is not standard and carries the risk of early bleeding and stroke, as well as the potential for late stenosis at the anastomotic site. 3 Artifi cial tracheal implantation causes anastomotic stenosis, luminal stenosis, infection, dislocation, and migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Reimplantation is not standard and carries the risk of early bleeding and stroke, as well as the potential for late stenosis at the anastomotic site. 3 Artifi cial tracheal implantation causes anastomotic stenosis, luminal stenosis, infection, dislocation, and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new technique for tracheal compression including reinforcement and suspension has been reported. 2 Although many articles have reported these treatments, the treatment strategy is not standardized because of the heterogeneity of these patients' conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other scaffold materials like 3D-prints and bio-syntheses, rib cartilage is easier to be obtained and higher histocompatibility, and its transplant approach is more simple as well as less cost. Takekawa et al [6] reported two teenagers of severe chest deformity suffered from TM caused by innominate artery compression. Through autologous cartilage graft and muscle flap suspension,airway obstruction was obviously released.…”
Section: Discussionmentioning
confidence: 99%
“…There are several surgical interventions for tracheomalacia owing to innominate artery compression, including transection, suspension and reimplantation of the innominate artery, and suspension and external reinforcement of the trachea [2,[9][10][11][12][13]. Tsugawa et al [2] indicated that transection of the innominate artery was useful in managing tracheomalacia owing to innominate artery compression caused by the anatomical relationships in pediatric patients with neuromuscular disorders.…”
Section: E3mentioning
confidence: 98%